Deproteinized bovine bone mineral in marginal defects at implants installed immediately into extraction sockets: an experimental study in dogs - Caneva, Marco [UNESP]; Botticelli, Daniele [UNESP]; Pantani, Fabio [UNESP]; Baffone, Gabriele M. [UNESP]; Rangel, Idelmo Garcia [UNESP]; Lang, Niklaus P. (Wiley-Blackwell, 2012)
Aim: To evaluate the influence of deproteinized bovine bone mineral (DBBM) particles concomitant with the placement of a collagen membrane on alveolar ridge preservation and on osseointegration of implants placed into alveolar sockets immediately after tooth extraction. Material and methods: The pulp tissue of the mesial roots of 3P3 was removed in six Labrador dogs and the root canals were filled. Flaps were elevated in the right side of the mandible, and the buccal and lingual alveolar bony plates were exposed. The third premolar was hemi-sectioned and the distal root was removed. A recipient site was prepared and an implant was placed lingually. After implant installation, defects of about 0.6mm wide and 3.1mm depth resulted at the buccal aspects of the implant, both at the test and at the control sites. The same surgical procedures and measurements were performed on the left side of the mandible. However, DBBM particles with a size of 0.25-1mm were placed into the remaining defect concomitant with the placement of a collagen membrane. Results: All implants were integrated into mature bone. No residual DBBM particles were detected at the test sites after 4 months of healing. Both the test and the control sites showed buccal alveolar bone resorption, 1.8 +/- 1.1 and 2.1 +/- 1mm, respectively. The most coronal bone-to-implant contact at the buccal aspect was 2 +/- 1.1 an 2.8 +/- 1.3mm, at the test and the control sites, respectively. This difference in the distance was statistically significant. Conclusion: The application of DBBM concomitant with a collagen membrane to fill the marginal defects around implants placed into the alveolus immediately after tooth extraction contributed to improved bone regeneration in the defects. However, with regard to buccal bony crest preservation, a limited contribution of DBBM particles was achieved.
Keywords: animal study; bone healing; collagen membrane; deproteinized bovine bone mineral; extraction socket; implant dentistry; osseointegration; regeneration; ridge preservation